METTL3-dependent DLG2 inhibits the malignant progression of cervical cancer by inactivating the Hippo/YAP signaling - Mei Pu; Xia Xiao; Shasha Lv; Daqing Ran; Qian Huang; Mingming Zhou; Qirong Lei; Lingshuang Kong; Qing Zhang (Hereditas)
Abstract Background Discs large homolog 2 (DLG2) has been implicated in cancer development, yet its role in cervical cancer remains unclear. This study aims to explore the regulatory mechanism of DLG2 in cervical cancer and its clinical implications. Methods Quantitative reverse transcription polymerase chain reaction and western blotting assays were employed to detect RNA and protein expression, respectively. Colony formation assay, 5-Ethynyl-2’-deoxyuridine assay, flow cytometry, and transwell assays were conducted for cell functional analysis. A xenograft mouse model assay was performed to analyze tumor tumorigenesis in vivo. m6A RNA immunoprecipitation assay was used to analyze the association of METTL3 and DLG2. Results DLG2 was underexpressed in cervical cancer tissues and cells. Elevating DLG2 levels significantly suppressed cervical cancer cell proliferation, migration, and invasion, while promoting apoptosis. Additionally, DLG2 overexpression led to the deactivation of the Hippo/YAP signaling pathway. In vivo, DLG2 overexpression was shown to reduce tumor formation. We also discovered that METTL3 destabilized DLG2 mRNA through an m6A-dependent mechanism. Moreover, lowering DLG2 expression mitigated the effects of METTL3 silencing on cervical cancer cell malignancy. Conclusion DLG2 acted as a tumor suppressor in cervical cancer by inhibiting the Hippo/YAP signaling pathway. The METTL3-dependent regulation of DLG2 mRNA stability could be a critical factor in cervical cancer progression.